Agir enseignant et dynamique du groupe dans la classe : vers une mise en complémentarité au service d’un climat propice aux apprentissages - Rémi Poymiro; Jean Vannereau (Recherches en Éducation)
This article focuses on understanding the difficulties faced by beginning teachers in regulating the classroom climate. First of all, it sets out the context in which the training accompaniment of second-degree teachers is carried out. Then he constructed a complementarity between the concepts of professional gestures and the posture of teachers and the field of group dynamics in order to better observe and understand the processes of acting teacher in the area of classroom climate regulation.